Insight into wastewater decontamination using polymeric adsorbents - Alaba, P.A. (Elsevier Ltd, 2018)
The use of polymeric adsorbent for decontamination of various sources of water was critically reviewed. This arises from the alarming increase in water scarcity in many parts of the world due to increase in population, which exerts immense pressure on the available water resources. Treatment of wastewater, stormwater and seawater via series of technological pathways like adsorption, desalination, advanced oxidation and solid-phase microextraction constitute new strategies for removal of toxins, antibiotics, complex matrix samples, and heavy metals for sustainable production of potable drinking water. This study reviewed the use of polymeric adsorbents such as nano-magnetic polymers (NMPs), polysaccharides, extracellular polymeric substances (EPS), and covalent organic polymers (COPs) for effective decontamination of water. These materials were critically analyzed with emphasis on their characteristics, strengths, drawbacks, as well as the enhancement techniques. Furthermore, the mechanisms of adsorption involved were also discussed. This review shows that polymeric adsorbents have demonstrated remarkable removal efficiency for several contaminants. Â© 2018 Elsevier Ltd